Tick bite anaphylaxis: Incidence and management in an Australian emergency department. (21st July 2013) - Rappo, Tristan B; Cottee, Alice M; Ratchford, Andrew M; Burns, Brian J
Abstract: Objectives: Ticks are endemic to the eastern coastline of Australia. The aim of the present study is to describe the incidence of tick bites in such an area, the seasonal and geographical distribution, the incidence of anaphylaxis due to tick bite and its management. Methods: We retrospectively analysed emergency presentations of patients with tick bites to Mona Vale Hospital on Sydney's Northern Beaches over a 2 year period from 1 January 2007 to 1 January 2009. We recorded the geographical and seasonal distribution of tick bites as well as the symptoms from tick bite and its emergency management. Results: We report over 500 cases of tick bites presenting to a single New South Wales hospital over a 2 year period, of which 34 resulted in anaphylaxis. Cutaneous symptoms were the most common feature associated with anaphylaxis (32/34, 94%). Forty per cent (13/34) of patients with tick bite anaphylaxis had a history of allergy or previous anaphylaxis. Seventy‐six per cent (26/34) of patients were administered adrenaline either prior to presenting or in the ED, while 97% (33/34) were treated with steroids. Fifty‐three per cent were referred to an immunologist and only one‐quarter were discharged with an adrenaline auto‐injector. Conclusion: We report 34 cases of tick bite anaphylaxis over a 2 year period at a single hospital in a tick endemic area. The variation in the presenting symptoms and signs, as well as in management highlights the need for increased awareness for tick bite management in tick endemic areas.